Multi-objective optimization of auxiliary wireless power supply system for maglev trains - CHENG Long; DONG Kan; WANG Shuo (机车电传动)
During the operation of maglev trains approaching stations, the electric energy generated by the linear generators propels the trains but is insufficient to meet the power demands of onboard equipment. Traditional contact power supply methods have shown deficiencies in various aspects, such as high installation and maintenance costs, as well as the safety risks associated with exposed live conductors. In contrast, wireless power transfer (WPT) technology eliminates the need for physical cable connections, allowing maglev trains to operate without mechanical contact and enhancing the safety, economic efficiency, and environmental adaptability of their auxiliary power supply system. This paper focuses on the optimized design for the magnetic coupling mechanism and resonant compensation circuit, addressing specific requirements of auxiliary WPT systems in maglev train applications including high power demands and efficiency requirements. A finite element model of a magnetic coupling mechanism with a single-transmitter multiple-receiver (STMR) configuration was established. The operational characteristics of three resonant compensation topologies (S/S, LCC/LCC, LCC/S) for WPT systems were compared and analyzed. A global multi-objective optimization design strategy was introduced based on the concept ofPareto optimal solutions. Furthermore, an 8.5 kW auxiliary WPT system prototype was built for verification. The experimental results demonstrated the proposed optimization scheme in meeting the design requirements of WPT systems for maglev trains, with an energy transfer efficiency of up to 91.9%.